Sclerosing Stromal Tumor of the Ovary - Güngör, Tayfun; Altınkaya, Özlem; Özsoy, Mesut; Akbay, Serap; Sırvan, Levent; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: Sclerosing stromal tumor (SST) of the ovary is a rare ovarian disease with prevalence of 1.5 % to 6 % of ovarian stromal tumors. These tumors appear solid and are very vascular and therefore give the impression of a malignant tumor. STUDY DESIGN: Clinical data of five patients with SST are presented. All of the patients underwent surgical treatment. Diagnosis of SST is revealed by final histopathological examinations. RESULTS: Among the five cases encountered the mean age at presentation was 30.2 years. The clinical presentation varied from menorrhagia (1 case), irregular menses (1 case), pelvic pain (2 cases) and asymptomatic mass (1 case). Ca 125 level was elevated in only one case. CONCLUSION: SSTs should be considered in young women with menstrual irregularity who have hypervascular solid and cystic adnexal masses. Though the tumor appears malignant, since it occurs in young women, care should be taken before embarking on radical surgery.